Predictability of adverse outcomes in hypertensive disorders of pregnancy: a multicenter prospective cohort study. (2nd October 2021) - Vasquez, Daniela N.; Das Neves, Andrea V.; Aphalo, Vanina M.; Vidal, Laura; Moseinco, Miriam; Lapadula, Jorge; Santa-Maria, Analía; Zakalik, Graciela; Gomez, Raúl A.; Capalbo, Mónica; Fernandez, Claudia; Agüero-Villareal, Enrique; et al.
ABSTRACT: Objectives: To explore variables associated with adverse maternal/fetal/neonatal outcomes among pregnant/postpartum patients admitted to ICU for hypertensive disorders of pregnancy (HDP). Methods: Multicenter, prospective, national cohort study. Results: Variables independently associated with maternal/fetal/neonatal mortality among 172 patients were as follows: Acute Physiology and Chronic Health Evaluation-II (APACHE-II)(OR1.20[1.06–1.35]), gestational age (OR0.698[0.59–0.82]) and aspartate aminotransferase (AST)(OR1.004[1.001–1.006]). Positive likelihood ratio for headache, epigastric pain, and visual disturbances to predict composite adverse outcomes were 1.23(1.16–1.30), 0.76(0.59–1.02), and 1.1(0.98–1.2), respectively. Conclusions: Maternal/fetal mortality due to HDP was independently associated with severity of illness on admission, gestational age, and elevated AST. Accuracy of clinical symptoms to predict composite adverse outcomes was low.